A comparative study of the clinical effects of simultaneous and delayed surgery for the treatment of cranial and maxillofacial fractures with multiple systemic injuries - TAN Xi⁃tao; CHI Yu⁃feng; WANG Wei; WANG Pei (口腔疾病防治, 2016)
Objective To investigate the clinical effect of simultaneous and delayed surgery with cranial and maxil⁃ lofacial fractures with multiple systemic injuries. Methods From January 2013 to January 2015, 85 cases of patients with multiple systematic injuries and maxillofacial fractures were treated in our hospital. Fractures of the maxillofacial parts and other parts of body were divided into 2 groups, 37 cases of delayed surgery, 48 of simultaneous surgery. The degree of neurologic impairment, occlusion, mouth opening, the time in hospital, postoperative complication rate were compared between two groups. Results There was no significant difference in the prognosis of the patients on the item of Glasgow outcome scale (GOS) in the simultaneous group and the delay group at 3 months after the operation (Z = ⁃1.545, P = 0.122). The excellent occlusion rate of simultaneous group (93.75%) was significantly higher than the delayed group (75.68%) (c2 = 5.630, P = 0.018). The mouth opening of simultaneous group (34.5 ± 3.6) mm is signifi⁃ cantly higher than the delayed group (28.9 ± 3.3) mm (c2 = 7.370, P < 0.001); The time in hospital of simultaneous group (28.5 ± 5.2) d was significantly shorter than delayed group (40.1 ± 5.7) d (c2 = 9.778, P < 0.001). The postopera⁃tive complication rate of simultaneous group (8.33%) was significantly lower than that in the delay group (24.32%) (c2 = 4.124, P = 0.042). Conclusion In the case of patients with appropriate trauma degree, for patients with cranial and maxillofacial fractures and multiple systematic injury, we can take multiple department combined surgical treatment, which can shorten hospitalization time. It is beneficial to the recovery of patients􀆳 maxillofacial appearance and function. And combined operation will not affect the other combined injuries in the treatment effect.